Lingkungan Kerja 'Work from Home' selama Pandemi Covid-19: Apakah Berdampak pada Kinerja Karyawan? - Annatasya, Dewi; Rosalina, Sylvia Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
The Covid-19 Pandemic occurred from 2020 to 2021 forced many organizations to arrange their employes to do works from home. The question is, does the new working system affect employee performance? The authors proposed that the new working system, work environment and work culture influence job performance through job satisfaction. To test that notion, the authors conducted a study in the Lembaga Layanan Pendidikan Tinggi Wilayah III by recruiting 47 employees as respondents who were work from home during the pendemic. Data processing using the Partial Least Squares–Structural Equation Model with the help of SmartPLS 3 shows that organizational culture has a positive effect on performance but has no effect on job satisfaction. The work environment directly determines employee satisfaction but indirectly does not affect employee performance improvement. Job satisfaction has a positive and significant influence on improving performance. The work environment has a positive effect on job satisfaction. Organizational culture and job satisfaction positively and significantly affect employee performance. The work environment has a positive but not significant effect on employee performance. In short, the new environment generates no effect on job performance. Future research should involve more respondents.